Detecção sorológica e molecular de patógenos transmitidos por carrapatos em cães de uma área endêmica para Leishmania infantum do estado do Mato Grosso do Sul - de Sousa, Keyla Carstens Marques [UNESP]; André, Marcos Rogério [UNESP]; Herrera, Heitor Miraglia; de Andrade, Gisele Braziliano; Jusi, Marcia Mariza Gomes [UNESP]; Ladislau, Luciana; Barreto, Wanessa Teixeira Gomes; Machado, Rosangela Zacarias [UNESP]; de Oliveira, Gilson Pereira [UNESP] (My University, 2013)
Tick-borne pathogens affect a wide range of vertebrate hosts. To identify tick-borne pathogens among dogs from Campo Grande, MS, Brazil testing seropositive for Leishmania infantum (syn. L. chagasi), a serological and molecular study was conducted to detect Ehrlichia canis, Anaplasma platys and Babesia vogeli in 60 serum and spleen samples. A confirmatory diagnosis of L. infantum based on serological and molecular assays was also performed, as was sequence alignment and phylogenetic analysis to assess the identity of the parasite species infecting these animals. IgG antibodies to Ehrlichia spp., B. vogeli and L. infantum were found, respectively, in 39 (65%), 49 (81.6%) and 60 (100%) of the sampled dogs. Twenty-seven (45%), fifty-four (90%), fifty-three (88.3%), two (3.3%) and one (1.6%) dog were positive, respectively, for E. canis, Leishmania spp., Leishmania donovani complex, Babesia sp. and Anaplasma sp. in PCR assays. After sequencing, the amplicons showed 99% of identity with E. canis, B. vogeli, A. platys and Leishmania chagasi isolates. The findings of this study indicate that L. infantum-seropositive dogs from Campo Grande are exposed to multiple tick-borne pathogens, which should therefore be included in the differential diagnosis of dogs with clinical suspicion of leishmaniasis.
Molecular and serological detection of tick-borne pathogens in dogs from an area endemic for Leishmania infantum in Mato Grosso do Sul, Brazil
Keywords: Anaplasma platys; Babesia vogeli; Co-infection; Dogs; Ehrlichia canis; Leishmania infantum